Validity Evidence of the Work-Family Conflict Scale for Public Security Professionals - Francisco A. Coelho Júnior; Mariana S. Rodrigues; Ana Gabriela D. Mauch; Gislene S. L. Lopes; Maria José Chambel; Cláudio V. Torres; Francisco G. L. Macedo (Psicologia: Teoria e Pesquisa, 2023)
Abstract The aim of this article is to present evidence of validity for the ‘work-family conflict scale’ with a sample of 10,383 professionals working in Brazilian public security. Cross-validation procedures were applied through the definition of two subsamples, exploratory and confirmatory factor analyses were performed. All ethical procedures were followed. The results found in both the exploratory factor analysis (‘Work Interference with Family’ Factor, with factor loadings between .91 and .81 and alpha of .93, and ‘Family Interference with Work’ Factor, with factor loadings between .96 and .71 and alpha of .90) and the confirmatory analysis (χ2/df <5; CFI >.98; TLI >.98; RMSEA <.10) demonstrate robust evidence of validity, indicating the use of the scale in other organizational contexts.